Knowledge, attitude, practices and concerns regarding COVID-19 vaccination in Nepal – A descriptive cross-sectional study - Timalsina , Punjita; Khadka, Merina; Saud , Mithu; Bhuju , Champa; Raut , Jyotshna; Pratel , Jamuna; Poudel , Sudha; Khatri, Elina (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: COVID-19 shifted from a 2020 pandemic to a 2023 end of emergency. Though the pandemic ended, the virus persists, and global vaccination remains vital. Initial vaccination rates were high, but subsequent doses declined. This study assesses the population’s knowledge, attitude, practice, and concerns about COVID-19 vaccines. Methods: Web-based descriptive cross-sectional study was conducted using convenience sampling technique. Google data collection forms with digital consent were developed based on 39-item standard questionnaire. Ethical approval was obtained from Nepal Health Research Council. Using SPSS version 22.0, descriptive statistical analysis was done. Results: A Total of 424 respondents were included in the study. The mean age of respondents was 28.35+8.01 years. 66.04% respondents were young adults aged 18-29 years and 83.02% resided in urban areas. 84.67% respondents were willing to receive the COVID-19 vaccine in the future, though only 56.84% were willing to pay for the vaccine if needed. Among those willing to pay, 58.51% were willing to pay less than NRs. 400. 91.98% demonstrated adequate knowledge about COVID-19 vaccination, exceeding threshold score of 13.5. All respondents exhibited favorable attitudes towards COVID-19 vaccination with a median score of 4.00. Contrary to favourable attitude, 83.73% respondents had negative concerns towards vaccination. Conclusion: The study found that people have adequate knowledge and favourable attitude towards COVID-19 vaccination. However, there are still concerns regarding vaccination that should be addressed when planning future vaccination strategies